2022
DOI: 10.3390/rs14184440
|View full text |Cite
|
Sign up to set email alerts
|

Is an NWP-Based Nowcasting System Suitable for Aviation Operations?

Abstract: The growth of air transport demand expected over the next decades, along with the increasing frequency and intensity of extreme weather events, such as heavy rainfalls and severe storms due to climate change, will pose a tough challenge for air traffic management systems, with implications for flight safety, delays and passengers. In this context, the Satellite-borne and IN-situ Observations to Predict The Initiation of Convection for ATM (SINOPTICA) project has a dual aim, first to investigate if very short-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Scientific and technological progress has led to an increase in the capabilities of weather forecasting over the past 40 years. Mazzarella et al [22] investigated whether NWP-based weather forecasts at a high-resolution (including data assimilation) could improve the capability of the prediction of extreme events in order to understand if such models could be suitable for supporting air traffic management. They found that, for a specific test case, the model was able to provide forecasts at least 1 h in advance, giving ATM operators sufficient time to manage air traffic and calculate new landing trajectories prior to an extreme event.…”
Section: The Lam Cosmo Modelmentioning
confidence: 99%
“…Scientific and technological progress has led to an increase in the capabilities of weather forecasting over the past 40 years. Mazzarella et al [22] investigated whether NWP-based weather forecasts at a high-resolution (including data assimilation) could improve the capability of the prediction of extreme events in order to understand if such models could be suitable for supporting air traffic management. They found that, for a specific test case, the model was able to provide forecasts at least 1 h in advance, giving ATM operators sufficient time to manage air traffic and calculate new landing trajectories prior to an extreme event.…”
Section: The Lam Cosmo Modelmentioning
confidence: 99%
“…Scientific and technological progresses have led to increasing the capabilities of weather forecasting over the past 40 years. Mazzarella et al [20] investigated if NWP-based weather forecasts at high-resolution (including data assimilation) can improve the capability of predicting extreme events, in order to understand if such models can be suitable to support air traffic management. They found that, for a specific test case, the model was able to provide forecasts at least 1 h in advance, giving ATM operators sufficient time to manage air traffic and calculate new landing trajectories prior to an extreme event.…”
Section: The Lam Cosmo Modelmentioning
confidence: 99%
“…A suggested solution to enhance forecast accuracy is the increase of numerical weather forecast model resolutions, to account for turbulent wind characteristics and wind shear in the lower troposphere over complex terrains [2]. However, these models show limitations, especially in small-scale patterns and physical processes, that are markedly pronounced in complex terrain and pose a risk to aviation [5,6]. Machine Learning (ML) techniques, exemplified by models like Convolutional Neural Networks (CNN) that use Deep Learning (DL) networks, emerge as an alternative approach.…”
Section: Introductionmentioning
confidence: 99%